Edukasi Penanganan Perubahan Iklim Siswa Sekolah Dasar melalui Media Komik mitigasi bencana berbasis CRT - Indri Yani; Lungguh Halira; M. Taufik; Indirwan Indirwan (Jurnal Penelitian Pendidikan IPA, 2025)
Climate change is a global challenge that impacts human life and the environment, which requires effective education, especially for the younger generation. This research aimed to develop comic media as an educational tool to address climate change through the Culturally Responsive Teaching (CRT) approach, with a focus on disaster mitigation for elementary school students. This study implemented a Research and Development (R&D) method using the ADDIE model and was conducted with fourth-grade students at SDIT Bunaya, Bogor with 20 students as the participants. The results showed that the average student understanding of climate change before the learning process was 72.25, which increased to 91.75 after the intervention. These findings indicate that the use of comic media effectively enhances students’ understanding of climate change and disaster mitigation, while also fostering caring attitudes toward the environment. Moreover, the comic media provides an engaging, interactive, and contextual learning experience. It not only improves students’ environmental literacy but also serves as a culturally relevant science education tool that supports sustainable development